Empathy and Communication: A Model of Empathy Development - Valente, Faith (Journal of New Media and Mass Communication, 2016)
Empathy is an important communication skill that has been shown to affect both individual knowledge acquisition and interpersonal relationships. How empathy develops and subsequently influences human interactions, and the consequences associated with those interactions, is the focus of this study. I examine the empathetic perceptions of upper division undergraduate college students and integrate their lived experience with empathy related factors discussed in the literature to describe a model of empathy development. The results suggest people can learn to communicate more efficiently and effectively by developing empathy in them-selves as well as in other people. More specifically, the findings indicate empathy is a function of several internal and external elements beyond biological and environmental antecedents. Respondents associated four internal themes with increased empathetic understanding: emotional sharing, positive relationships, mutual regard, and personal genuineness. Respondents also identified three external themes that moderated the strength or direction of their empathetic perceptions: the perceived similarity, relevance, and availability of the person being observed. Each of these seven themes is explicated in order to discern how one person might better empathize with another or enhance the ability of other people to empathize with them. The practical implications for more empathetic communication are explored, as are suggestions for future research.